2006
DOI: 10.1021/nl052452l
|View full text |Cite
|
Sign up to set email alerts
|

Interface Effect on Ferroelectricity at the Nanoscale

Abstract: Interfaces play a critical role in nanoscale ferroelectricity. We perform a first-principles study of ultrathin KNbO(3) ferroelectric films placed between two metal electrodes, either SrRuO(3) or Pt. We show that bonding at the ferroelectric-metal interfaces imposes severe constraints on the displacement of atoms, destroying the bulk tetragonal soft mode. If the interface bonding is sufficiently strong, the ground-state represents a ferroelectric domain with an interface domain wall, driven by the intrinsic op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
165
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(182 citation statements)
references
References 31 publications
15
165
2
Order By: Relevance
“…of the top and bottom interfaces. 8,30,32,[57][58][59][60][61] In the present work, the extrapolation lengths of the top and bottom interface are same, i.e., ␦ I-T = ␦ I-B = ␦ I . 61 Note that ␦ I-T and ␦ I-B have different physical origins, such as different topbottom electrodes, interface effect and polarization switching etc., which may be obtained from first-principle calculations 8,52,55 and a combination of first-principle and phenomenological calculations.…”
Section: ͑6͒mentioning
confidence: 80%
See 2 more Smart Citations
“…of the top and bottom interfaces. 8,30,32,[57][58][59][60][61] In the present work, the extrapolation lengths of the top and bottom interface are same, i.e., ␦ I-T = ␦ I-B = ␦ I . 61 Note that ␦ I-T and ␦ I-B have different physical origins, such as different topbottom electrodes, interface effect and polarization switching etc., which may be obtained from first-principle calculations 8,52,55 and a combination of first-principle and phenomenological calculations.…”
Section: ͑6͒mentioning
confidence: 80%
“…In absence of an external electric field, the internal electric field comes from the depolarization field produced by polarization screening charges in the metal electrodes and the inhomogeneous polarization distribution near interfaces. Here the homogeneous polarization distribution is affected by complex factors, 1,8,[28][29][30][31][32][33][34][35] such as surface discontinuity of the ferroelectric layer, 8,27,31,32 and Schottky barriers at interface, etc. 10,14,27,29 Theories and experiments on FNCs taking various forms such as nanodisks ͑ND͒, nanorods ͑NR͒, nanowires ͑NW͒, and nanotubes ͑NT͒ have indicated that their phase-transition or near-phase-transition properties are very sensitive to the applied stress.…”
Section: ͑Pzt͒mentioning
confidence: 99%
See 1 more Smart Citation
“…1 A FTJ consists of two metal electrodes separated by a nm-thick ferroelectric barrier which allows electron tunneling through it. Recent experimental 2-4 and theoretical [5][6][7][8] studies of perovskite ferroelectric oxide thin films have demonstrated that ferroelectricity persists down to a nanometer scale, which makes it possible to use ferroelectrics as functional tunnel barriers in FTJs. Contrary to ferroelectric capacitors where leakage currents are detrimental to the device performance, 9 the conductance of a FTJ is the functional characteristic of the device.…”
Section: Introductionmentioning
confidence: 99%
“…The ferroelectric film in this heterostructure is about 66 Å thick, well exceeding the critical thickness for ferroelectricity ͑see, e.g., Ref. 25 14 To reduce the highly intensive computational efforts to a manageable level, we only use three unit cells of BaTiO 3 in the slice structure shown in Fig. 1͑a͒.…”
mentioning
confidence: 99%